Preparation method and application of MnFeNi-based medium-entropy porous lithium-sulfur battery composite material

By using MnFeNi-based medium-entropy porous composite materials in lithium-sulfur battery cathode materials and using Joule heat treatment technology to prepare materials with rich carbon defects and hierarchical pore structures, the problems of slow reaction kinetics and low preparation efficiency of lithium-sulfur batteries are solved. problem, realizing lithium-sulfur batteries with high capacity, long life and high rate performance.

CN118814010BActive Publication Date: 2025-01-21SHANDONG HAIHUA GRP CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411264334.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-01-21
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

The existing lithium-sulfur battery positive electrode materials have slow reaction kinetics during the electrochemical process, resulting in insufficient actual capacity and poor cycle stability, and the traditional preparation methods are low in efficiency and high energy consumption.

Method used

Using MnFeNi-based medium-entropy porous composite materials, zinc nitrate, manganese chloride, iron nitrate, nickel nitrate and potassium salts were dissolved in methanol, followed by ultrasonic reaction and vacuum drying, followed by Joule heat treatment to prepare a composite material with rich carbon defects. and composite materials with hierarchical porous structures.

Benefits of technology

This method optimizes the adsorption structure of LiPS, promotes the diffusion and catalysis of polysulfides on the surface of composite materials, reduces the reaction barrier, increases the reaction rate, significantly improves the cycle life and rate capability of lithium-sulfur batteries, and improves battery performance. specific capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118814010B_ABST
    Figure CN118814010B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a MnFeNi-based medium-entropy porous lithium-sulfur battery composite material and its application, which belongs to the technical field of preparing positive electrode materials for lithium-sulfur batteries. The present invention uses potassium salt as a pore collapse inhibitor and defect inducer, combined with Joule heat treatment technology, to induce the first solid mixed with potassium salt to form a large number of defects during the carbonization process, and inhibit the collapse of the pores at high temperatures, which is beneficial to anchoring and dispersing metal elements, and then preparing a MnFeNi-based medium-entropy catalyst with atomic dispersion characteristics. Through the synergistic effect between different atoms, the adsorption structure of LiPS is optimized, the diffusion and catalysis of polysulfides on the surface of the electrocatalyst are promoted, the reaction barrier of polysulfides can be reduced, and its reaction speed can be increased, which significantly improves the cycle life and rate performance of lithium-sulfur batteries, and improves the specific capacity of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of a MnFeNi-based medium-entropy porous lithium-sulfur battery composite material, belonging to the technical field of preparation of lithium-sulfur battery positive electrode materials. Background Art

[0002] Lithium-sulfur (Li-S) batteries are considered promising contenders for the next generation of energy storage systems with their theoretical capacity of 1675 mAh / g and excellent energy density of 2600 Wh / kg. However, they still face significant technical barriers to overcome in the commercialization process, among which the main challenging issues are the insulation of elemental sulfur, the severe shuttle effect of polysulfides, the high reaction energy barrier, and the slow redox reaction kinetics, which lead to insufficient actual capacity and poor cycle stability.

[0003] Li-S batteries involve multi-step reactions with different intermediates in the electrochemical process, which requires the cathode materials to interact appropriately with these intermediates. In addition, Li-S batteries have two opposite processes: discharge and charge. Therefore, the cathode materials in Li-S batteries must be able to work bidirectionally to ensure high Coulombic efficiency of the charge and discharge reactions, which makes the design of Li-S battery cathode materials more challenging. In the prior art, atomically dispersed metal catalysts with independently exposed metal centers and adjustable electronic structures have theoretically 100% atomic utilization efficiency and extremely high catalytic activity. However, the isolated metal center of the single-atom lithium-sulfur battery composite can only coordinate with one sulfur atom of LiPS (lithium polysulfide) to form a metal-sulfur bond, and this end-face adsorption structure is not conducive to the stable anchoring of LiPS. In addition, the end-face adsorption structure also limits the activation of the SS bond in LiPS, resulting in excessively high reaction energy barriers. Therefore, it will be an effective strategy to synergistically optimize the adsorption capacity and reaction kinetics by using multiple metal atoms to adjust the spatial and electronic structure of the active site, thereby adjusting the adsorption structure with LiPS.

[0004] The Chinese invention patent with publication number CN113054183A discloses a method for preparing a CoNi bimetallic organic framework-derived carbon-sulfur composite material. The method first synthesizes a CoNi bimetallic organic framework (MOF) material, and then calcines it in a tubular furnace to obtain a CoNi bimetallic MOF-derived carbon material. It can be seen from the specific surface area diagram of the patent that the adsorption curve belongs to a type II adsorption curve, indicating that the material is a macroporous material and does not belong to a multi-level pore structure material rich in mesopores; in addition, the use of traditional tubular furnace calcination methods is prone to cause problems such as collapse of the pore structure (smaller pore size range) and agglomeration of metal atoms, resulting in a decrease in electrochemical performance.

[0005] The Chinese invention patent with publication number CN116960331A discloses a method for preparing a sulfurized polyacrylonitrile positive electrode material for lithium-sulfur batteries. The method is to react a variety of metal salts with organic ligands to obtain a precursor, then place the precursor in a tubular furnace for calcination, and then acid etch to obtain a target product, and finally the target product and sulfur powder and polyacrylonitrile are subjected to secondary calcination in a tubular furnace to obtain a positive electrode material. The preparation of this method is cumbersome, and not only secondary calcination but also acid treatment is required; wherein secondary calcination will increase energy consumption, and although acid treatment will etch the material to obtain a wider pore range, the waste acid generated will cause environmental pollution. In addition, the addition of polyacrylonitrile is to introduce more carbon sources to increase its conductivity, but this method does not require the introduction of additional carbon sources. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing a MnFeNi-based medium-entropy porous lithium-sulfur battery composite material, which can solve the problem of slow polysulfide reaction kinetics caused by end-face adsorption of single-atom lithium-sulfur battery composite materials and the low efficiency and high energy consumption of the traditional composite material preparation process. The method optimizes the adsorption of LiPS by the medium-entropy porous lithium-sulfur battery composite material, promotes the diffusion and catalysis of polysulfide (Li2S) on the surface of the MnFeNi-based medium-entropy porous lithium-sulfur battery composite material, reduces the reaction barrier of Li2S, increases the reaction rate, effectively improves the overall performance of lithium-sulfur batteries, and has broad industrial prospects.

[0007] To achieve this object, the technical solution of the present invention is:

[0008] A method for preparing a MnFeNi-based medium-entropy porous lithium-sulfur battery composite material comprises the following steps:

[0009] (1) adding zinc nitrate, manganese chloride, iron nitrate, nickel nitrate and potassium salt into methanol to dissolve to obtain a first mixed solution; adding 2-methylimidazole and potassium salt into methanol to dissolve to obtain a second mixed solution;

[0010] (2) mixing the first mixed solution with the second mixed solution, reacting the mixture by ultrasonication at room temperature for 4-8 hours, centrifuging and vacuum drying to obtain a first solid;

[0011] (3) Grinding the first solid object into 200-300 mesh powder, placing the first solid object powder in a groove of a graphite sample stage of a Joule heat heating device, and then performing Joule heat treatment under a protective atmosphere of nitrogen or argon to obtain a second solid object; washing and vacuum drying the second solid object to obtain a MnFeNi-based medium-entropy porous lithium-sulfur battery composite material.

[0012] Furthermore, in step (1), the potassium salt is one of potassium carbonate, potassium bicarbonate, potassium citrate and potassium chloride.

[0013] Furthermore, in the step (1), the ratio of zinc nitrate, manganese chloride, ferric nitrate, nickel nitrate, potassium salt and methanol in the first mixed solution is 1mmol:1-1.5mmol:1-1.5mmol:1-1.5mmol:10-20mmol:50mL; the ratio of 2-methylimidazole, potassium salt and methanol in the second mixed solution is 4-10mmol:10-20mmol:50mL.

[0014] Furthermore, in step (2), the vacuum drying conditions are: drying temperature 50-80°C, and drying time 5-10h.

[0015] Furthermore, in step (3), the conditions of Joule heat treatment are: heat treatment temperature 600-2000°C, heating rate 1500-2500°C / s, and Joule heat treatment times 4-10 times. The Joule heat treatment is heating from room temperature to the target temperature and then naturally cooling to room temperature, which is represented as one time.

[0016] Furthermore, in step (3), the washing conditions are: washing with deionized water and methanol three to five times respectively; and the vacuum drying conditions are: drying temperature 50-80° C., and drying time 5-10 h.

[0017] Another object of the present invention is to provide an application of a MnFeNi-based medium-entropy porous lithium-sulfur battery composite material prepared by the above method, which is applied to the positive electrode of a lithium-sulfur battery.

[0018] The beneficial effects of the present invention are:

[0019] (1) The present invention uses Joule heat treatment technology. Compared with the traditional calcination method, the equipment operation is simple, the preparation efficiency is high, and the energy consumption is low. The Joule heat treatment technology has the characteristics of rapid heating and cooling, which is not only conducive to retaining a large number of carbon defects and multi-level pore structures generated during the ligand pyrolysis and providing more sites for anchoring metal atoms, but also can inhibit the agglomeration of metal atoms during the calcination process.

[0020] (2) The present invention uses potassium salt as a pore collapse inhibitor and defect inducer. During the chemical in situ synthesis of ZIF-8, a portion of the potassium salt will be wrapped into the interior of ZIF-8, and another portion of the potassium salt will be adsorbed in the pores on the surface of ZIF-8. After vacuum drying, the salt adsorbed in the surface pores will crystallize into small crystals, acting as a filler for the pores, preventing the collapse of the pores under high-temperature calcination, and having a synergistic effect with the Joule heat treatment technology; and the potassium salt wrapped in the interior of ZIF-8 will enter the carbon lattice during the high-temperature calcination process to form a large number of carbon defects. Therefore, the addition of potassium salt is conducive to obtaining rich carbon defects and multi-level pore structures, thereby anchoring and dispersing metal elements, thereby preparing an atomically dispersed MnFeNi-based medium-entropy porous lithium-sulfur battery composite material.

[0021] (3) The present invention grinds the first solid object into 200-300 mesh powder, which helps to evenly heat the material during the Joule heat treatment and prevents local overheating from causing collapse of material pores, agglomeration of metal atoms, and collapse of the structure.

[0022] (4) The MnFeNi-based mesenterotropic porous lithium-sulfur battery composite material prepared by the present invention has excellent electrical conductivity and conductive properties, can provide abundant active sites for anchoring and dispersing metal atoms, can achieve synergistic effects between different atoms, optimize the adsorption structure of LiPS, promote the diffusion and catalysis of polysulfide on the surface of MnFeNi-based mesenterotropic porous lithium-sulfur battery composite material, reduce the reaction barrier of polysulfide, increase its reaction rate, significantly improve the cycle life and rate capability of lithium-sulfur battery, and improve the specific capacity of the battery.

[0023] (5) The MnFeNi-based intermediate entropy porous lithium-sulfur battery composite material prepared by the present invention has a carbon defect structure (I D / I G ) content and pore size range are 0.91-1.01 and 4-64nm, respectively, and the application performance in the positive electrode of lithium-sulfur batteries is outstanding. Especially at a high rate of 1C, the initial specific capacity of the lithium-sulfur battery is as high as 870.5-1097.2mAh / g, and the capacity retention rate after 500 cycles is 71.3-75.6%; at a high rate of 3C, the initial specific capacity is as high as 630.3-850.3mAh / g, and the recovery rate when switching from 3C to 0.2C is 91.25-93.33%. Therefore, the MnFeNi-based medium-entropy porous lithium-sulfur battery composite material shows excellent high-rate capacity, high stability, high rate, and reversibility in the lithium-sulfur battery reaction, and has broad industrial prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is a Raman spectrum of the MnFeNi-based intermediate entropy porous lithium-sulfur battery composite material obtained in step (3) of Example 1;

[0025] Figure 2 This is a spherical aberration-corrected high-angle annular dark-field scanning transmission electron microscopy image of the MnFeNi-based medium-entropy porous lithium-sulfur battery composite material obtained in step (3) of Example 1;

[0026] Figure 3 Electrochemical long cycle performance test diagram of a lithium-sulfur battery positive electrode prepared from the MnFeNi-based medium-entropy porous lithium-sulfur battery composite material obtained in step (3) of Example 1 at a rate of 1C;

[0027] Figure 4 High rate test graph of a lithium-sulfur battery positive electrode prepared from the MnFeNi-based medium-entropy porous lithium-sulfur battery composite material obtained in step (3) of Example 1 at 0.2-3C. DETAILED DESCRIPTION

[0028] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that a person skilled in the art can better understand and implement the present invention, but the protection scope of the present invention is not limited thereto.

[0029] Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commercially available materials; unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those generally understood by those skilled in the art.

[0030] In a specific embodiment of the present invention, the Joule heat heating device used is composed of a gas circuit device, a vacuum pump, a graphite sample stage, a temperature control system, and a data acquisition system. The model is CIS-JH3.3-P, the output voltage is 0-40V, the output current is 0-500A, the temperature measurement range is 0-3000℃, the power supply is 380V / 30A, and the current ramp time is 1ms. Example 1

[0031] (1) Add 1 mmol zinc nitrate, 1.25 mmol manganese chloride, 1.25 mmol iron nitrate, 1.25 mmol nickel nitrate, and 15 mmol potassium bicarbonate to 50 mL methanol, and dissolve them by ultrasonication to obtain a first mixed solution; add 6 mmol 2-methylimidazole and 15 mmol potassium bicarbonate to 50 mL methanol, and dissolve them by ultrasonication to obtain a second mixed solution;

[0032] (2) mixing the first mixed solution with the second mixed solution, subjecting the mixture to ultrasonic reaction at room temperature for 6 h, centrifuging the mixture, and vacuum drying the mixture at 65° C. for 6 h to obtain a first solid;

[0033] (3) Grind the first solid object into 300 mesh powder, then place 0.2 g of the first solid powder in the groove of the graphite sample stage of a Joule heat heating device, and then perform Joule heat treatment 6 times under a nitrogen protective atmosphere, with a Joule heat treatment temperature of 1500°C and a Joule heat treatment heating rate of 2000°C / s to obtain a second solid object; wash the second solid object with deionized water and methanol four times respectively, and vacuum dry it at 65°C for 6 hours to obtain a MnFeNi-based medium-entropy porous lithium-sulfur battery composite material.

[0034] The MnFeNi-based medium entropy porous lithium-sulfur battery composite material obtained in step (3) was subjected to Raman spectroscopy test, spherical aberration corrected high-angle annular dark field scanning transmission electron microscopy test, and nitrogen total adsorption (N2-BET) pore size distribution test, respectively. Figure 1 , Figure 2 , Table 1, where the pore size distribution test results of N2-BET are the full pore distribution results based on the NLDFT model.

[0035] Depend on Figure 1 It can be seen that I D / I G The ratio is the D band (1353 cm -1 peaks around 1587 cm) and ordered sp2 hybridized carbon G band (1587 cm -1 ) peak area ratio, I D / I G The value of I is 1.01, D / I G It is much larger than 0.6 of conventional materials, indicating that the MnFeNi-based intermediate entropy porous lithium-sulfur battery composite material has a rich carbon defect structure; Figure 2 It can be seen that Mn, Fe, and Ni atoms are well dispersed on the carbon material substrate. When the bright spots are not aggregated, they are separated bright spots, indicating that the MnFeNi-based mesotropic porous lithium-sulfur battery composite material has good atomic dispersion characteristics; as shown in Table 1, the MnFeNi-based mesotropic porous lithium-sulfur battery composite material has a multi-level pore structure with rich mesopores and macropores, and the pore size range is 5-64nm, which is conducive to the adsorption of polysulfides and improves the reaction rate.

[0036] The MnFeNi-based intermediate entropy porous lithium-sulfur battery composite material obtained in step (3) is used for lithium-sulfur battery testing, including the following application steps:

[0037] ① The MnFeNi-based medium-entropy porous lithium-sulfur battery composite material and sublimated sulfur were mixed in a mass ratio of 1:3 and loaded into a reactor lined with polytetrafluoroethylene, and heated at 160°C for 16 hours to solidify sulfur to obtain a solidified positive electrode material;

[0038] ②In an inert atmosphere glove box, the solid sulfur positive electrode material, polypropylene porous membrane separator and electrolyte (a mixed solution of 1 mol / L lithium bis(trifluoromethanesulfonyl)imide and 0.2 mol / L lithium nitrate with 1,3-dioxolane and 1,2-dimethoxyethane (the volume ratio of 1,3-dioxolane to 1,2-dimethoxyethane is 1:1)) are assembled into a button cell. The battery is tested for electrochemical long cycle performance at 1C rate and high rate test at 0.2-3C on the CT-4008-5A6V system. The test results are shown in Figure 3 and Figure 4 .

[0039] Depend on Figure 3 It can be seen that the first-cycle discharge capacity at a rate of 1C is 1097.2 mAh / g. After 500 cycles, the capacity remains at 850.3 mAh / g, and the capacity retention rate is 75.4%. It has good initial specific capacity, cycle stability and high capacity attenuation rate.

[0040] Depend on Figure 4 It can be seen that at the high charge and discharge rate of 0.2-3C, the capacity reached 1350.25mAh / g and 850.3mAh / g at 0.2C and 3C respectively. When switched to 0.2C, the capacity reached 1260.25mAh / g, and the recovery rate reached 93.33%, indicating that it has highly reversible electrochemical properties and exhibits good rate performance. Example 2

[0041] (1) Add 1 mmol zinc nitrate, 1 mmol manganese chloride, 1 mmol iron nitrate, 1 mmol nickel nitrate, and 10 mmol potassium carbonate to 50 mL methanol, and dissolve them by ultrasonication to obtain a first mixed solution; add 4 mmol 2-methylimidazole and 10 mmol potassium carbonate to 50 mL methanol, and dissolve them by ultrasonication to obtain a second mixed solution;

[0042] (2) mixing the first mixed solution with the second mixed solution, subjecting the mixture to ultrasonic reaction at room temperature for 4 h, centrifuging the mixture, and vacuum drying the mixture at 50° C. for 10 h to obtain a first solid;

[0043] (3) Grind the first solid into 200 mesh powder, place 0.2 g of the first solid powder in the groove of the graphite sample stage of the Joule heat heating device, and then perform Joule heat treatment 4 times under a nitrogen protective atmosphere, with a Joule heat treatment temperature of 2000°C and a Joule heat treatment heating rate of 2500°C / s to obtain a second solid; wash the second solid with deionized water and methanol three times respectively, and vacuum dry it at 50°C for 10 hours to obtain a MnFeNi-based medium-entropy porous lithium-sulfur battery composite material.

[0044] The MnFeNi-based medium-entropy porous lithium-sulfur battery composite material obtained in step (3) was subjected to Raman spectroscopy test and N2-BET pore size distribution test, see Table 1.

[0045] As shown in Table 1, the I D / I G The value of I is 0.91. D / I G It is much larger than 0.6 of conventional materials, indicating that the MnFeNi-based mesenterotropic porous lithium-sulfur battery composite material has a rich carbon defect structure; the MnFeNi-based mesenterotropic porous lithium-sulfur battery composite material has a multi-level pore structure with rich mesopores and macropores, with a pore size range of 4-55nm, which is conducive to the adsorption of polysulfides and improves the reaction rate.

[0046] The MnFeNi-based medium-entropy porous lithium-sulfur battery composite material obtained in step (3) was used for lithium-sulfur battery testing. The testing method was the same as Example 1. The test results are shown in Table 1.

[0047] As can be seen from Table 1, the first-cycle discharge capacity at a rate of 1C is 870.5mAh / g. After 500 cycles, the capacity retention rate is 71.3%, which has good initial specific capacity, cycle stability and high capacity attenuation rate; at a high charge and discharge rate of 0.2-3C, the initial specific capacity at a rate of 3C is 630.3mAh / g, and the capacity recovery rate reaches 94.52% when switched to 0.2C, indicating highly reversible electrochemical properties and showing good rate performance. Example 3

[0048] (1) 1 mmol zinc nitrate, 1.5 mmol manganese chloride, 1.5 mmol iron nitrate, 1.5 mmol nickel nitrate, and 20 mmol potassium citrate were added to 50 mL methanol and dissolved by ultrasonication to obtain a first mixed solution; 8 mmol 2-methylimidazole and 20 mmol potassium citrate were added to 50 mL methanol and dissolved by ultrasonication to obtain a second mixed solution;

[0049] (2) mixing the first mixed solution with the second mixed solution, subjecting the mixture to ultrasonic reaction at room temperature for 8 h, centrifuging the mixture, and vacuum drying the mixture at 80° C. for 5 h to obtain a first solid;

[0050] (3) Grind the first solid object into 250 mesh powder, then place 0.2 g of the first solid powder in the groove of the graphite sample stage of the Joule heat heating device, and then perform Joule heat treatment 10 times under a nitrogen protective atmosphere, with a Joule heat treatment temperature of 600°C and a Joule heat treatment heating rate of 1500°C / s to obtain a second solid object; wash the second solid object with deionized water and methanol five times respectively, and vacuum dry it at 80°C for 5 hours to obtain a MnFeNi-based medium-entropy porous lithium-sulfur battery composite material.

[0051] The MnFeNi-based medium-entropy porous lithium-sulfur battery composite material obtained in step (3) was subjected to Raman spectroscopy test and N2-BET pore size distribution test, see Table 1.

[0052] As shown in Table 1, the I D / I G The value of I is 0.93. D / I G It is much larger than 0.6 of conventional materials, indicating that the MnFeNi-based mesenterotropic porous lithium-sulfur battery composite material has a rich carbon defect structure; the MnFeNi-based mesenterotropic porous lithium-sulfur battery composite material has a multi-level pore structure with rich mesopores and macropores, with a pore size range of 5-58nm, which is conducive to the adsorption of polysulfides and improves the reaction rate.

[0053] The MnFeNi-based medium-entropy porous lithium-sulfur battery composite material obtained in step (3) was used for lithium-sulfur battery testing. The testing method was the same as Example 1. The test results are shown in Table 1.

[0054] As can be seen from Table 1, the first-cycle discharge capacity at a rate of 1C is 925.3mAh / g. After 500 cycles, the capacity retention rate is 73.4%, which has good initial specific capacity, cycle stability and high capacity attenuation rate; at a high charge and discharge rate of 0.2-3C, the initial specific capacity at a rate of 3C is 680.5mAh / g, and the capacity recovery rate reaches 91.25% when switched to 0.2C, indicating highly reversible electrochemical properties and showing good rate performance. Example 4

[0055] (1) Add 1 mmol zinc nitrate, 1.1 mmol manganese chloride, 1.1 mmol iron nitrate, 1.1 mmol nickel nitrate, and 12 mmol potassium chloride to 50 mL methanol, and dissolve them by ultrasonication to obtain a first mixed solution; add 5 mmol 2-methylimidazole and 12 mmol potassium chloride to 50 mL methanol, and dissolve them by ultrasonication to obtain a second mixed solution;

[0056] (2) mixing the first mixed solution with the second mixed solution, subjecting the mixture to ultrasonic reaction at room temperature for 6 h, centrifuging the mixture, and vacuum drying the mixture at 75° C. for 7 h to obtain a first solid;

[0057] (3) Grind the first solid object into 300 mesh powder, then place 0.2 g of the first solid powder in the groove of the graphite sample stage of a Joule heat heating device, and then perform Joule heat treatment 6 times under an argon protective atmosphere, with a Joule heat treatment temperature of 1500°C and a Joule heat treatment heating rate of 1800°C / s to obtain a second solid object; wash the second solid object with deionized water and methanol four times respectively, and vacuum dry it at 75°C for 7 hours to obtain a MnFeNi-based medium-entropy porous lithium-sulfur battery composite material.

[0058] The MnFeNi-based medium-entropy porous lithium-sulfur battery composite material obtained in step (3) was subjected to Raman spectroscopy test and N2-BET pore size distribution test, see Table 1.

[0059] As shown in Table 1, the I D / I G The value of I is 0.97. D / I G It is much larger than 0.6 of conventional materials, indicating that the MnFeNi-based mesenterotropic porous lithium-sulfur battery composite material has a rich carbon defect structure; the MnFeNi-based mesenterotropic porous lithium-sulfur battery composite material has a multi-level pore structure with rich mesopores and macropores, with a pore size range of 5-62nm, which is conducive to the adsorption of polysulfides and improves the reaction rate.

[0060] The MnFeNi-based medium-entropy porous lithium-sulfur battery composite material obtained in step (3) was used for lithium-sulfur battery testing. The testing method was the same as Example 1. The test results are shown in Table 1.

[0061] As can be seen from Table 1, the first-cycle discharge capacity at a rate of 1C is 990.5mAh / g. After 500 cycles, the capacity retention rate is 75.6%, which has good initial specific capacity, cycle stability and high capacity attenuation rate; at a high charge and discharge rate of 0.2-3C, the initial specific capacity at a rate of 3C is 750.3mAh / g, and the capacity recovery rate reaches 93.20% when switched to 0.2C, indicating highly reversible electrochemical properties and showing good rate performance. Comparative Example 1

[0062] The difference between Comparative Example 1 and Example 1 is that the heating device in step (3) is different, the Joule heat heating device is replaced with a tube furnace, and the other steps remain unchanged. The specific operation is as follows:

[0063] 0.2 g of the first solid powder was placed in a tubular furnace and calcined under a nitrogen protective atmosphere at a calcination temperature of 1500° C. and a heating rate of 5° C. / min. The reaction was kept warm for 2 hours to obtain a MnFeNi-based medium-entropy porous lithium-sulfur battery composite material.

[0064] The obtained MnFeNi-based medium-entropy porous lithium-sulfur battery composite material was subjected to Raman spectroscopy test and N2-BET pore size distribution test, and the test results are shown in Table 1.

[0065] As shown in Table 1, the I D / I G The value and pore size range are 0.75, 3-55nm, I D / I G The pore size distribution is much smaller than 1.01 and 5-64 nm of Example 1, indicating that the MnFeNi-based medium-entropy porous lithium-sulfur battery composite material prepared by the Joule heat treatment technology has more abundant carbon defects and multi-level pore structure. These defect sites can better anchor and disperse metal sites, and the multi-level pore structure is conducive to the adsorption of polysulfides, thereby showing higher catalytic activity and better stability. In addition, by comparing Comparative Example 1 with Example 1, it can be seen that the MnFeNi-based medium-entropy porous lithium-sulfur battery composite material obtained by the Joule heat treatment technology has more carbon defects and multi-level pore structure, mainly relying on the rapid heating and cooling characteristics of the Joule heat treatment technology, which inhibits the disappearance of these carbon defects and multi-level pore structure.

[0066] The obtained MnFeNi-based medium-entropy porous lithium-sulfur battery composite material was used for lithium-sulfur battery testing. The testing method was the same as Example 1, and the test results are shown in Table 1.

[0067] It can be seen from Table 1 that the MnFeNi-based medium-entropy porous lithium-sulfur battery composite material of Comparative Example 1 has a first-cycle discharge capacity of 668.3 mAh / g at a rate of 1C. After 500 cycles, the capacity retention rate is 48.4%, the initial specific capacity at 3C is 450.3 mAh / g, and the capacity recovery rate when switching from 3C to 0.2C is 82.34%, which is much smaller than the result of Example 1. Comparative Example 2

[0068] The difference between Comparative Example 2 and Example 1 is that no potassium salt is added in step (1), and the other steps remain unchanged.

[0069] The obtained MnFeNi-based medium-entropy porous lithium-sulfur battery composite material was subjected to Raman spectroscopy test and N2-BET pore size distribution test, and the test results are shown in Table 1.

[0070] As shown in Table 1, the ID / I G The value and pore size range are 0.65, 3-40nm, I D / I G The pore size distribution is much smaller than 1.01 and 5-64 nm of Example 1, indicating that the first solid prepared by adding potassium salt and then the MnFeNi-based medium-entropy porous lithium-sulfur battery composite material prepared by Joule heat treatment technology has richer carbon defects and multi-level pore structure. This is because in the process of in-situ chemical synthesis of ZIF-8, part of the potassium salt will enter the interior of ZIF-8, and part of the potassium salt will be adsorbed in the pores on the surface of ZIF-8. After vacuum drying, the salt adsorbed in the surface pores will crystallize into small crystals, acting as a filler for the pores, preventing the collapse of the pores under high-temperature calcination; and the potassium salt wrapped into the interior of ZIF-8 will enter the carbon lattice during high-temperature calcination, forming a large number of carbon defects; therefore, the addition of potassium salt is conducive to obtaining rich carbon defects and multi-level pore structure, and then anchoring and dispersing metal elements, thereby preparing MnFeNi-based medium-entropy porous lithium-sulfur battery composite materials with atomic dispersion characteristics.

[0071] The obtained MnFeNi-based medium-entropy porous lithium-sulfur battery composite material was used for lithium-sulfur battery testing. The testing method was the same as Example 1, and the test results are shown in Table 1.

[0072] It can be seen from Table 1 that the MnFeNi-based medium-entropy porous lithium-sulfur battery composite material of Comparative Example 2 has a first-cycle discharge capacity of 450.8 mAh / g at a rate of 1C. After 500 cycles, the capacity retention rate is 40.5%, the initial specific capacity at 3C is 210.3 mAh / g, and the capacity recovery rate when switching from 3C to 0.2C is 81.38%, which is much smaller than the result of Example 1.

[0073] Comparative Example 3

[0074] The difference between Comparative Example 3 and Example 1 is that no iron nitrate is added in step (1), and the other steps remain unchanged to obtain a MnNi-based porous lithium-sulfur battery composite material.

[0075] The obtained MnNi-based porous lithium-sulfur battery composite material was subjected to Raman spectroscopy test and N2-BET pore size distribution test, and the test results are shown in Table 1.

[0076] It can be seen from Table 1 that the I D / I G The value and pore size range are 0.79, 4-52nm, I D / I GThe pore size distribution is much smaller than 1.01 and 5-64 nm in Example 1, indicating that the MnFeNi-based medium-entropy porous lithium-sulfur battery composite material has richer carbon defects and a multi-level pore structure. These defect sites can better anchor and disperse metal sites, and the multi-level pore structure helps the adsorption of polysulfides, thereby exhibiting higher catalytic activity and better stability.

[0077] The obtained MnNi-based porous lithium-sulfur battery composite material was used for lithium-sulfur battery testing. The testing method was the same as Example 1. The test results are shown in Table 1.

[0078] As shown in Table 1, the MnNi-based porous lithium-sulfur battery composite material of Comparative Example 3 has a first-cycle discharge capacity of 745.3 mAh / g at a rate of 1C. After 500 cycles, the capacity retention rate is 62.7%, the initial specific capacity at 3C is 498.6 mAh / g, and the capacity recovery rate at 3C switching to 0.2C is 85.72%, which is much smaller than the result of Example 1, indicating that ferric nitrate affects the electrochemical performance by affecting the carbon defect structure and multi-level pore structure. In addition, there is a synergistic effect between Fe, Mn, and Ni atoms, which can significantly enhance the chemical adsorption and catalytic conversion of polysulfides, thereby significantly promoting the kinetic process of sulfur redox reaction and improving the overall performance of lithium-sulfur batteries. Comparative Example 4

[0079] The difference between Comparative Example 4 and Example 1 is that no iron nitrate or nickel nitrate is added in step (1), and the other steps remain unchanged to obtain a Mn-based porous lithium-sulfur battery composite material.

[0080] The obtained Mn-based porous lithium-sulfur battery composite material was subjected to Raman spectroscopy test and N2-BET pore size distribution test, and the test results are shown in Table 1.

[0081] It can be seen from Table 1 that the I D / I G The value and pore size range are 0.71, 4-47nm, I D / I G The pore size distribution is much smaller than 1.01 and 5-64 nm in Example 1, indicating that the MnFeNi-based medium-entropy porous lithium-sulfur battery composite material has richer carbon defects and a multi-level pore structure. These defect sites can better anchor and disperse metal sites, and the multi-level pore structure helps the adsorption of polysulfides, thereby exhibiting higher catalytic activity and better stability.

[0082] The obtained Mn-based porous lithium-sulfur battery composite material was used for lithium-sulfur battery testing. The testing method was the same as Example 1. The test results are shown in Table 1.

[0083] As shown in Table 1, the Mn-based porous lithium-sulfur battery composite material of Comparative Example 4 has a first-cycle discharge capacity of 589.4 mAh / g at a rate of 1C. After 500 cycles, the capacity retention rate is 52.1%, the initial specific capacity at 3C is 348.5 mAh / g, and the capacity recovery rate at 3C switched to 0.2C is 84.42%, which is much smaller than the result of Example 1, indicating that iron nitrate and nickel nitrate affect the electrochemical performance by affecting the carbon defect structure and multi-level pore structure. In addition, there is a synergistic effect between Fe, Mn, and Ni atoms, which can significantly enhance the chemical adsorption and catalytic conversion of polysulfides, thereby significantly promoting the kinetic process of sulfur redox reaction and improving the overall performance of lithium-sulfur batteries.

[0084]

[0085] As can be seen from the above, compared with Comparative Example 1, the MnFeNi-based medium-entropy porous lithium-sulfur battery composite material prepared in Example 1 has a larger I D / I G Value(I D / I G The larger the value, the more carbon defects there are) and the wider pore size distribution, which is mainly because the Joule heat treatment technology has the characteristics of rapid temperature rise and fall, which inhibits the disappearance of these defects and multi-level pore structure; Example 1 and Comparative Example 2 show that potassium salt, as a pore collapse inhibitor and defect inducer, can induce the ligand to form a large number of defects during the carbonization process and inhibit the collapse of the pores at high temperatures, and has a synergistic effect with the Joule heat treatment technology to form a MnFeNi-based medium entropy porous lithium-sulfur battery composite material with rich defects and multi-level pore structure; Example 1 and Comparative Examples 3 and 4 show that the addition of iron nitrate and nickel nitrate will affect the carbon defects and multi-level pore structure, and these defect sites can better anchor and disperse metal sites, and the multi-level pore structure helps to adsorb polysulfides, thereby showing higher catalytic activity and better stability. In addition, there is a synergistic effect between Fe, Mn, and Ni atoms, which can significantly enhance the chemical adsorption of polysulfides and their catalytic conversion, thereby significantly promoting the kinetic process of sulfur redox reaction and improving the overall performance of lithium-sulfur batteries.

[0086] The above embodiments are intended to illustrate the essential content of the present invention, but are not intended to limit the protection scope of the present invention. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a MnFeNi-based medium-entropy porous lithium-sulfur battery composite material, characterized in that: The following steps are involved: (1) adding zinc nitrate, manganese chloride, iron nitrate, nickel nitrate and potassium salt into methanol to dissolve and obtain a first mixed solution; Add 2-methylimidazole and potassium salt into methanol to dissolve, to obtain a second mixed solution; (2) mixing the first mixed solution with the second mixed solution, reacting the mixture by ultrasonication at room temperature for 4-8 hours, centrifuging and vacuum drying to obtain a first solid; (3) grinding the first solid object into a powder of 200-300 mesh, placing the first solid object powder in a groove of a graphite sample stage of a Joule heat heating device, and then performing Joule heat treatment under a protective atmosphere of nitrogen or argon to obtain a second solid object; washing and vacuum drying the second solid object to obtain a MnFeNi-based medium-entropy porous lithium-sulfur battery composite material; In the step (3), the conditions of the Joule heat treatment are: heat treatment temperature 600-2000°C, heating rate 1500-2500°C / s, and Joule heat treatment times 4-10 times.

2. The method for preparing the MnFeNi-based intermediate entropy porous lithium-sulfur battery composite material according to claim 1, characterized in that: In the step (1), the potassium salt is one of potassium carbonate, potassium bicarbonate, potassium citrate and potassium chloride.

3. The method for preparing the MnFeNi-based intermediate entropy porous lithium-sulfur battery composite material according to claim 1, characterized in that: In the step (1), the ratio of zinc nitrate, manganese chloride, ferric nitrate, nickel nitrate, potassium salt and methanol in the first mixed solution is 1mmol:1-1.5mmol:1-1.5mmol:1-1.5mmol:10-20mmol:50mL; the ratio of 2-methylimidazole, potassium salt and methanol in the second mixed solution is 4-10mmol:10-20mmol:50mL.

4. The method for preparing the MnFeNi-based intermediate entropy porous lithium-sulfur battery composite material according to claim 1, characterized in that: In the step (2), the vacuum drying conditions are: drying temperature 50-80°C, and drying time 5-10h.

5. The method for preparing the MnFeNi-based intermediate entropy porous lithium-sulfur battery composite material according to claim 1, characterized in that: In the step (3), the washing conditions are: washing with deionized water and methanol three to five times respectively; the vacuum drying conditions are: drying temperature 50-80°C, drying time 5-10h.

6. An application of a MnFeNi-based intermediate entropy porous lithium-sulfur battery composite material prepared by the preparation method according to any one of claims 1 to 5, characterized in that: Apply it to the positive electrode of lithium-sulfur batteries.

Citation Information

Patent Citations

  • Preparation method of CoNi bimetal organic framework derived carbon-sulfur composite material

    CN113054183A

  • Preparation method of sulfurized polyacrylonitrile positive electrode material for lithium-sulfur battery

    CN116960331A

  • Preparation method of lithium / sulfur battery positive electrode material

    CN108539142A

  • Improved design of solid-state lithium-sulfur battery positive electrode, and related preparation method

    CN111834660A